Electron-electron drag in crystals with multivalley band - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Mobility of electrons in multivalley bands of Si and Ge is considered with due regard for intervalley drag. It is shown that drag sufficiently diminishes electron mobility at low temperatures. This effect is clearer pronounced in germanium than in silicon.